Resistance and wave impedance - Dwojak, Adam (Instal, 2020)
Despite the built-in alarm system, depending on the owner, the pre-insulated networks either function or without actual supervision, or supervision is based on devices with insulation resistance measurement. Occasionally, As a rule, wave impedance measurements, i.e. reflectometric measurements, are performed only in oriented companies. And sometimes they are helpful in assessing the state of isolation. The considerations in this article are essentially about the impulse system without felt pads, although they can also be used in a resistance system
Keywords: pre-insulated heating networks; alarm system